The Prenatal Diagnosis and Clinical Outcomes of Fetuses With 15q11.2 Copy Number Variants: A Case Series of 36 Patients - Kang, Jessica; Lee, Chien-Nan; Su, Yi-Ning; Lin, Ming-Wei; Tai, Yi-Yun; Hsu, Wen-Wei; Huang, Kuan-Ying; Chen, Chi-Ling; Hung, Chien-Hui; Lin, Shin-Yu (Frontiers in Medicine, 2021)
Prenatal genetic counseling of fetuses diagnosed with 15q11.2 copy number variants (CNVs) involving the BP1–BP2 region is difficult due to limited information and controversial opinion on prognosis. In total, we collected the data of 36 pregnant women who underwent prenatal microarray analysis from 2010 to 2017 and were assessed at National Taiwan University Hospital. Comparison of the maternal characteristics, prenatal ultrasound findings, and postnatal outcomes among the different cases involving the 15q11.2 BP1–BP2 region were presented. Out of the 36 fetuses diagnosed with CNVs involving the BP1–BP2 region, five were diagnosed with microduplications and 31 with microdeletions. Among the participants, 10 pregnant women received termination of pregnancy and 26 gave birth to healthy individuals (27 babies in total). The prognoses of 15q11.2 CNVs were controversial and recent studies have revealed its low pathogenicity. In our study, the prenatal abnormal ultrasound findings were recorded in 12 participants and were associated with 15q11.2 deletions. No obvious developmental delay or neurological disorders were detected in early childhood.